2015
DOI: 10.1089/fpd.2015.1995
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping ofSalmonellaFood Isolates Suggests the Geographic Clustering of Serotype Telaviv

Abstract: Salmonella is commonly found in a variety of food products and is a major cause of bacterial foodborne illness throughout the world. In this study, we investigated the prevalence and diversity of Salmonella in eight different food types: sheep ground meat, cow ground meat, chicken meat, cow offal, traditional Sanliurfa cheese, unripened feta cheese, pistachios, and isot (a spice blend of dried red peppers specific to Sanliurfa), traditionally and commonly consumed in Turkey. Among 192 food samples, Salmonella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…After assessing all the information from the recovered publications, seventy-eight primary studies [6,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,…”
Section: Methodsmentioning
confidence: 99%
“…After assessing all the information from the recovered publications, seventy-eight primary studies [6,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,…”
Section: Methodsmentioning
confidence: 99%
“…Serovar Infantis, Enteritidis, Kentucky and Telaviv isolates were used, of which Infantis, Enteritidis and Kentucky serovars are among the most common isolated serovars in Turkey. Interestingly, Telaviv has also been commonly isolated from food samples in Turkey although it is among the rare serovars throughout D. Aksoy the world (Ozdemir & Acar 2014, Erol 1999, Durul et al 2015. The results showed that both the prolonged incubation period and the temperature effected the biofilm formation capacities depending on the serovars.…”
Section: Resultsmentioning
confidence: 98%
“…enterica strains (n =56), isolated from chicken meat, and cow ground meat and offal, were obtained from the Department of Food Engineering of the Middle East Technical University (METU, TURKEY) and in their previous study molecular confirmation of these strains was conducted by determining invA gene (F:5'-GAACCCTCAGTTTTTCAACGTTTC-3', R:5'-TAGCCGTAACAACCAATACAAATG-3') by PCR (Kim et al 2007) and serotyping of strains was performed using the White-Kauffmann-Le Minor scheme (Grimont and Weil 2007) at the laboratory of Public Health Agency of Turkey in Ankara. Antimicrobial resistance of fifty-six S. enterica isolates have been phenotypically determined by agar disk diffusion (CLSI 2016) test using eighteen antibiotics, including amikacin (AK) 30 μg, ampicillin (AMP) 10 μg, amoxicillin-clavulanic acid (AMC) 20/10 μg, cefoxitin (FOX) 30 μg, cephalothin (KF) 30 μg, ceftiofur (EFT) 30 μg, ceftriaxone (CRO) 30 μg, chloramphenicol (C) 10 μg, ciprofloxacin (CIP) 5 μg, ertapenem (ETP) 10 μg, gentamicin (GN) 10 μg, imipenem (IPM) 10 μg, kanamycin (K) 30 μg, nalidixic acid (N) 30 μg, streptomycin (S) 10 μg, sulfisoxazole (SF) 10 μg, sulfamethoxazole-trimethoprim (SXT) 10 μg, and tetracycline (T) 30 μg discs and also the antimicrobial gene resistance profiles of these strains have been investigated by screening 21 antimicrobial resistance genes shown in Table 1, encoding resistance against Class A beta-lactamase, ceftiofur, ceftriaxone, beta-lactamases, chloramphenicol, streptomycin, gentamicin, kanamycin, trimethoprim, sulfisoxazole, and tetracycline (Acar et al 2017, Durul et al 2015. The isolates that show resistance to three or more antibiotic classes (with resistance to at least one antibiotic from each class) were considered to be MDR.…”
Section: Bacteria and Their Characteristics (Serotypes And Antibacter...mentioning
confidence: 99%